Potret Kemampuan Nara Sumber Diklat Peningkatan Kualitas Guru Pendidikan Agama Islam (PAI) Se-Kalimantan Timur - Nurbayani, Etty (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2012)
In order to improve Islamic education teachers’ competence in East Kalimantan, quality improvement program has been conducted to both teachers and also non teachers (administration) of Islamic education in East Kalimantan. The training was conducted by Education Development Agency (LPTK) STAIN Samarinda, East Kalimantan. The expectation to have qualified teachers in Islamic education has to be hand in hand with instructors’ competence of the training. Qualified and skillful trainers can be a good reference for the participants to teach Islamic education to their students. Otherwise, participants will not obtain any specific skill related to Islamic education. The impact is there is no any change of instructional paradigm done by teachers. In general, trainers/instructors’ competence in the training (DIKLAT) held by STAIN Samarinda October 2011 can be classified in high level. It is indicated by score of 85, 6 which is taken from various variables; accomplishment target of the courses, material appropriateness, instructional method, process, and motivation.